CHANGEABILITY OF THE ICE COVER ON THE LAKES OF NORTHERN POLAND IN THE LIGHT OF CLIMATIC CHANGES - Skowron, Rajmund (Bulletin of Geography. Physical Geography Series, 2009)
The study is based upon instrumental observations of ice covers which formed on the lakes in northern Poland in the period 1956–2005 and records of air temperature measured at 9 meteorological stations in the period 1960–2005. Relations between mean dates of ice cover freeze-up, ice cover duration, maximum ice thickness, and also other properties of ice regime indicate obvious dependency upon air temperatures in winter months (December-February). Both air temperatures and main properties of ice covers revealed definite trends, showing the increase in air temperature in winter (0.04–0.06°C year-1), earlier disappearance of ice cover (0.5–0.6 day year-1), its shorter duration (0.6–0.7 day year-1), and decreases in maximum thickness of the ice cover (0.2–0.25 cm year-1). The author shows considerable statistical relations between main properties of the course of the ice cover, air temperatures in winter and the NAO winter indexes. Therefore, changeability of the ice covers on the lakes in northern Poland in the latter half of the twentieth century may be treated as another proof and an indirect indicator of climatic changes undergoing in this part of Europe.